Influence of ferrimagnetic resonance on conversion of electromagnetic energy by a YIG resonator into mechanical one - Komarova, G.L. (Radiotekhnika, 2021)
Using the method of physical modeling, an algorithm for calculating the force with which a standing electromagnetic wave acts on a ferrite sphere of arbitrary diameter placed in a constant magnetic field is obtained. The value of constant magnetic field intensity provides appearance of ferrimagnetic resonance. Dependence of the magnetic field of an electromagnetic wave in the middle of a ferrite sphere on the size of its resonant radius and spherical coordinates are studied. In the center of the ferrite sphere, the resonance radius of which is 4.2634 mm, the microwave magnetic field strength is 83796 times greater than the magnetic field strength in the incident plane polarized wave. Mean-square value of the magnetic field strength over the volume of the sphere increases 4.8 times. Standing wave, formed in a free space with power flow density of 622 kW/m2 and wavelength of 3.2 cm, reflects from metallic shield placed at a distance of λo/8 + nλo/2, n = 0, 1, 2, 3… measured from the center of ferrite sphere and impacts with force of 0,12 N on ferrite sphere with resonance radius of 4,2634 mm. The results of the calculated force acting on the YIG – resonator coincide with the experimental results given in the well-known works (the power flux density is 43 kW/m2, the radius of the ferrite sphere is 1.775 mm, the force is 6 ± 0.5 μN) within the measurement error. Application of spatial resonance, standing electromagnetic wave and YIG resonator allows to increase of energy conversion factor of microwave energy conversion into mechanic one 8,6·104 times in compare to application of ferrite cylinder only in known papers. The research results can be used by the developers of converters of microwave energy into mechanical energy.